PERLINDUNGAN HUKUM BAGI PARA PIHAK DALAM JUAL BELI TANAH DENGAN AKTA DI BAWAH TANGAN - Joko Sadewo (SOL JUSTICIA, 2019)
This study aims to determine how the legal protection for the parties in the sale and purchase of land with a deed under the hand, and what are the factors that cause people to buy and sell land with a deed under the hand. This research is a normative legal research that is prescriptive and technical or applied. The research approach uses the law approach and case approach. The type of research data is secondary data with primary and secondary legal materials. Data collection techniques such as literature study and data analysis techniques used are deductive. The results of this study explain that the legal protection of the parties in buying and selling with a deed under the hand, namely both parties, especially the seller acknowledges the existence of the sale and purchase agreement that is carried out, in this case the most important thing to admit is the seller. If both parties acknowledge that the agreement under the hand that has been done is considered perfect and the legal force of the deed under the hand will be the same as the authentic deed, If one of the parties denies that there has never been a sale and purchase then go back to the applicable Government Regulation as long as there is no other evidence to prove. And the factors that cause people to buy and sell with a deed under the hand of the community lacking understanding or even ignorance of the perpetrators of the transaction both the seller and the buyer of land regarding the provisions of applicable law.